Embracing transparency and openness in scholarly publishing: Insights from the Malaysian social sciences researchers - Razlan, Noor Masliana; Samsuddin, Samsul Farid; Abrizah, A. (Malaysian Journal of Library and Information Science, 2024)
The scholarly publishing landscape is changing fast with the rise of open science practices and increased expectations for transparency and rigour. However, there is a notable gap in understanding how the social science researchers are adopting transparency and openness in scholarly publishing (TOSP), given the emergence of open science practices. Therefore, this paper seeks to: (a) What do social science researchers interpret as "transparency and openness in scholarly publishing", and (b) How do social science researchers navigate and practise transparency and openness in their scholarly publishing? A cohort of the 100 most productive Malaysian-based social science researchers identified from the Web of Science database was invited to participate via email. The evidence reported here comes from 20 who agreed to be interviewed. The findings reveal that social science researchers conceptualise TOSP through seven key themes: Data transparency; practices; Methodological transparency; Embracing open access; Readiness for criticism and feedback; Reliable peer review process; Research ethics in data management; and Articulating research limitations. Additionally, the study emphasises nine TOSP practices that social scientists highlight, including sharing and connecting; publishing in affordable open access journals; authorship and publishing standards; international research collaboration; using open access repositories; adopting preprints; adhering to ethics and integrity; participating in the peer review process; and ensuring research reproducibility. This study underscores the importance of TOSP attributes in fostering transparency and openness, which in turn enhances the credibility and impact of social science research. Aligning with these principles enables researchers to contribute to more reliable and impactful scholarship in an evolving academic landscape.